A synthesis method of composite fiber reinforced cement-based material based on hybrid effect
By adopting a composite fiber reinforcement method with mixed effects in cement-based materials, combined with carbon nanotube grafted polyvinyl alcohol composite fiber, steel fiber and ultra-high molecular weight polyethylene fiber, the problem of weak performance of cement-based materials in terms of softening, cracking strength, flexural strength and compressive strength is solved, and the comprehensive performance of the material is significantly improved.
Patent Information
- Application Number
- CN202310198592.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-03
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-03-03
AI Technical Summary
Existing cement-based materials are weak in softening resistance, cracking strength, flexural strength and compressive strength.
Using a synthesis method of composite fiber-reinforced cement-based material based on mixed effect, a mixture effect is formed to improve material performance by mixing and stirring carbon nanotube-grafted polyvinyl alcohol composite fibers, steel fibers and ultra-high molecular weight polyethylene fibers.
It significantly improves the comprehensive properties of cement-based materials such as softening, flexural strength, and compressive strength, and enhances the toughness and weather resistance of the materials.
Smart Images

Figure CN116217172B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement, in particular to a method for synthesizing a composite fiber reinforced cement-based material based on a hybrid effect. Background Art
[0002] Ultramolecular weight polyethylene fiber has the advantages of high strength, low density, good insulation, etc., but its low heat bearing capacity and cold creep limit its application. It is used in the production of various industrial textiles, especially filter materials, tarpaulins, mesh belts and other products. It is also widely used in building materials such as cement concrete. Polyvinyl alcohol fiber is made of high-quality polyvinyl alcohol with high polymerization degree. The main characteristics of polyvinyl alcohol fiber are high strength, high modulus, low elongation, wear resistance, acid and alkali resistance, good weather resistance, and good affinity and bonding with cement, gypsum and other substrates. For example, the literature "Sulfate Erosion Resistance of Polyvinyl Alcohol Fiber Reinforced Cement-based Composites under Long-term Immersion" studied the effects of fiber and fly ash on the sodium sulfate erosion resistance of polyvinyl alcohol fiber reinforced cement-based composites under long-term immersion. The results show that the incorporation and good dispersion of fibers form a good network distribution structure in the cement matrix, which slows down the erosion rate of polyvinyl alcohol fiber cement composites in sodium sulfate solution.
[0003] Steel fiber is a high-performance steel fiber variety. It has the advantages of good adhesion, strong hardness, good corrosion resistance, etc. For example, the document "Experimental Study on Mechanical Properties of Steel Fiber Reinforced Cement-based Composite Materials" discloses compression and flexural tests on steel fiber cement-based composite materials of different shapes and different volume ratios. The results show that the addition of steel fiber does not significantly improve the compressive strength of the cement matrix, but significantly improves the flexural strength and bending toughness, and both increase with the increase of the steel fiber volume ratio, which has a toughening effect on the cement base and delays cracking.
[0004] This paper proposes a new type of steel fiber based on hybrid effect, high-performance carbon nanotube grafted polyvinyl alcohol composite fiber, and polyethylene fiber to enhance the comprehensive properties of cement-based materials such as cracking strength, flexural strength, and compressive strength. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a method for synthesizing a composite fiber-reinforced cement-based material based on a hybrid effect, which solves the problems of weak softening resistance, cracking strength, bending strength and compressive strength of cement.
[0007] (II) Technical solution
[0008] A method for synthesizing a composite fiber-reinforced cement-based material based on a hybrid effect, the method comprising:
[0009] (1) placing polyvinyl alcohol in a flask, adding acetone, triethylamine and p-toluenesulfonyl chloride thereto and stirring for reaction, concentrating under reduced pressure after the reaction, washing with ethanol and drying to obtain p-toluenesulfonate polyvinyl alcohol;
[0010] (2) dissolving p-toluenesulfonate polyvinyl alcohol and potassium phthalimide in a mass ratio of 1:0.15-0.3 in N,N-dimethylformamide, heating and reacting for 3-5 hours at a temperature of 100-140° C. under N2 protection, concentrating under reduced pressure after the reaction, adding the product to ethanol, adding hydrazine hydrate, heating to 80° C. and reflux reaction for 3-6 hours, rotary evaporation to remove the solvent, washing with ethanol and drying to obtain amino polyvinyl alcohol;
[0011] (3) adding the carboxylated carbon nanotubes into a flask containing toluene solvent, stirring evenly, then adding amino polyvinyl alcohol, N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and heating to react, filtering after the reaction, washing with ethanol and drying to obtain carbon nanotube-grafted polyvinyl alcohol;
[0012] (4) dispersing the carbon nanotube grafted polyvinyl alcohol in a dimethyl sulfoxide solvent, spinning in a wet spinning machine, squeezing the solution into a spinning hole at a spinning temperature of 60-80°C and a nitrogen pressure of 0.1-0.2 MPa, and entering a coagulation bath of methanol at -20 to -10°C. After the nascent fiber is coagulated in the coagulation bath, it is wound and rolled up, and coagulated after being soaked in methanol for 10-14 hours, and then naturally dried for 18-24 hours. The dried fiber is gradually heat-treated and stretched at a heat treatment temperature of 180-240°C and a stretching multiple of 10-14 times to obtain a high-performance carbon nanotube grafted polyvinyl alcohol composite fiber;
[0013] (5) First, silicate cement, fly ash powder, silica fume, and quartz sand are put into a mixer and stirred for 2-10 minutes to mix the dry materials evenly. Then, water and polycarboxylic acid water reducer are slowly added and stirred continuously to obtain a uniformly flowing cement slurry. The mixer is controlled to operate at a low speed. Then, carbon nanotube-grafted polyvinyl alcohol composite fibers, steel fibers, and ultra-high molecular weight polyethylene fibers are added thereto. The materials are fully stirred and dispersed evenly. The materials are layered and cast into test specimens. After curing at room temperature for 18-24 hours, the mold is removed. Then, the test specimens are moved to a standard curing room for curing for 7-28 days to obtain a composite fiber-reinforced cement-based material based on a hybrid effect.
[0014] Preferably, the mass ratio of polyvinyl alcohol, p-toluenesulfonyl chloride and triethylamine in (1) is 1:0.1-0.25:0.05-0.12.
[0015] Preferably, the reaction in (1) is carried out at room temperature for 3-6 hours.
[0016] Preferably, in (3), the mass ratio of carboxylated carbon nanotubes, amino polyvinyl alcohol, N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 1:2-5:1.5-4:0.8-2.5.
[0017] Preferably, the heating reaction temperature in (3) is 90-120° C., and the reaction time is 5-8 h.
[0018] Preferably, the mass ratio of silicate cement, fly ash powder, silica fume, quartz sand, water and polycarboxylate water reducer in (5) is 1:0.6-1:0.1-0.3:1-1.5:0.3-0.7:0.003-0.008.
[0019] Preferably, the volume parameters of the carbon nanotube grafted polyvinyl alcohol composite fiber, steel fiber, and ultra-high molecular weight polyethylene fiber in (5) are 0.6-1.5%, 0.3-0.6%, and 1-2% of the cement paste, respectively.
[0020] (III) Beneficial technical effects
[0021] Polyvinyl alcohol is reacted with p-toluenesulfonyl chloride to obtain p-toluenesulfonate polyvinyl alcohol, and the obtained product is then reacted with potassium phthalimide to obtain amino polyvinyl alcohol. The amino group of polyvinyl alcohol is used to react with carboxylated carbon nanotubes to obtain carbon nanotube-grafted polyvinyl alcohol. High-performance carbon nanotube-grafted polyvinyl alcohol composite fibers are obtained by spinning in a wet spinning machine. High-performance carbon nanotube-grafted polyvinyl alcohol composite fibers, steel fibers and ultra-high molecular weight polyethylene fibers are mixed and stirred and added to cement paste to obtain composite fiber-reinforced cement-based materials. The three fibers produce a hybrid effect in cement concrete, which improves the comprehensive properties of cement materials such as anti-softening, flexural strength, and compressive strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the synthesis method of amino polyvinyl alcohol. DETAILED DESCRIPTION
[0023] Example 1
[0024] (1) At room temperature, 2 g of polyvinyl alcohol is placed in a flask, 50 ml of acetone, 0.1 g of triethylamine, and 0.2 g of p-toluenesulfonyl chloride are added thereto, and the mixture is stirred for reaction for 3 h. After the reaction, the mixture is concentrated under reduced pressure, washed with ethanol, and dried to obtain p-toluenesulfonate polyvinyl alcohol;
[0025] (2) dissolving 5 g of p-toluenesulfonate polyvinyl alcohol and 1.1 g of potassium phthalimide in N,N-dimethylformamide, heating at 120° C. under N2 protection for 4 h, concentrating under reduced pressure after the reaction, adding the product to ethanol, adding hydrazine hydrate, heating to 80° C. and reflux for 4.5 h, removing the solvent by rotary evaporation, washing with ethanol and drying to obtain amino polyvinyl alcohol;
[0026] (3) adding 1 g of carboxylated carbon nanotubes into a flask filled with toluene solvent, stirring evenly, then adding 2 g of amino polyvinyl alcohol, 1.5 g of N,N'-dicyclohexylcarbodiimide and 0.8 g of 4-dimethylaminopyridine, and heating to 90°C for reaction for 5 h, filtering after the reaction, washing with ethanol and drying to obtain carbon nanotube-grafted polyvinyl alcohol;
[0027] (4) dispersing carbon nanotube grafted polyvinyl alcohol into dimethyl sulfoxide solvent, spinning in a wet spinning machine, squeezing the solution into the spinning hole at a spinning temperature of 70°C and a nitrogen pressure of 0.1 MPa, and entering a coagulation bath of -10°C methanol. After the nascent fiber is coagulated in the coagulation bath, it is wound and rolled up, and coagulated after being soaked in methanol for 14 hours, and then naturally dried for 22 hours. The dried fiber is gradually heat-treated and stretched at a heat treatment temperature of 210°C and a stretching multiple of 11 times to obtain a high-performance carbon nanotube grafted polyvinyl alcohol composite fiber;
[0028] (5) First, 50 kg of silicate cement, 35 kg of fly ash powder, 12 kg of silica fume, and 55 kg of quartz sand were put into a mixer and stirred for 6 minutes to mix the dry materials evenly. Then, 25 kg of water and 0.3 kg of polycarboxylic acid water reducer were slowly added and stirred continuously to obtain a uniformly flowing cement slurry. The mixer was controlled to operate at a low speed. Then, 1.5% of the volume of the cement slurry was added with carbon nanotube grafted polyvinyl alcohol composite fibers, 0.4% of the volume of the cement slurry was added with steel fibers, and 1.5% of the volume of the cement slurry was added with ultra-high molecular weight polyethylene fibers. The materials were fully stirred and dispersed evenly. The materials were layered and cast into test specimens. After curing at room temperature for 21 hours, the mold was removed. Then, the test specimens were moved to a standard curing room for curing for 28 days to obtain a composite fiber reinforced cement-based material based on the hybrid effect.
[0029] Example 2
[0030] (1) At room temperature, 2 g of polyvinyl alcohol was placed in a flask, 50 ml of acetone, 0.24 g of triethylamine, and 0.5 g of p-toluenesulfonyl chloride were added thereto, and the mixture was stirred for reaction for 4.5 h. After the reaction, the mixture was concentrated under reduced pressure, washed with ethanol, and dried to obtain p-toluenesulfonate polyvinyl alcohol;
[0031] (2) dissolving 5 g of p-toluenesulfonate polyvinyl alcohol and 1.5 g of potassium phthalimide in N,N-dimethylformamide, heating at 120° C. under N2 protection for 5 h, concentrating under reduced pressure after the reaction, adding the product to ethanol, adding hydrazine hydrate, heating to 80° C. and reflux for 4.5 h, removing the solvent by rotary evaporation, washing with ethanol and drying to obtain amino polyvinyl alcohol;
[0032] (3) adding 1 g of carboxylated carbon nanotubes into a flask containing toluene solvent, stirring evenly, then adding 5 g of amino polyvinyl alcohol, 4 g of N,N'-dicyclohexylcarbodiimide and 2.5 g of 4-dimethylaminopyridine, and heating to 110°C for reaction for 5 h, filtering after the reaction, washing with ethanol and drying to obtain carbon nanotube-grafted polyvinyl alcohol;
[0033] (4) dispersing the carbon nanotube grafted polyvinyl alcohol in a dimethyl sulfoxide solvent, spinning in a wet spinning machine, squeezing the solution into a spinning hole at a spinning temperature of 80°C and a nitrogen pressure of 0.2 MPa, and entering a coagulation bath of -10°C methanol. After the nascent fibers are coagulated in the coagulation bath, they are wound and rolled up, and coagulated after being immersed in methanol for 14 hours, and then naturally dried for 24 hours. The dried fibers are gradually heat-treated and stretched at a heat treatment temperature of 240°C and a stretching multiple of 14 times to obtain high-performance carbon nanotube grafted polyvinyl alcohol composite fibers;
[0034] (5) First, 50 kg of silicate cement, 40 kg of fly ash powder, 10 kg of silica ash, and 60 kg of quartz sand were put into a mixer and stirred for 6 minutes to mix the dry materials evenly. Then, 25 kg of water and 0.27 kg of polycarboxylic acid water reducer were slowly added and stirred continuously to obtain a uniformly flowing cement slurry. The mixer was controlled to operate at a low speed. Then, 1% of the volume of the cement slurry was added with carbon nanotube grafted polyvinyl alcohol composite fiber, 0.4% of the volume of the cement slurry was added with steel fiber, and 1.5% of the volume of the cement slurry was added with ultra-high molecular weight polyethylene fiber. The mixture was stirred and dispersed evenly. The materials were layered and cast into test specimens. After curing at room temperature for 21 hours, the mold was removed. Then, the test specimens were moved to a standard curing room for curing for 17 days to obtain a composite fiber reinforced cement-based material based on the hybrid effect.
[0035] Example 3
[0036] (1) At room temperature, 2 g of polyvinyl alcohol was placed in a flask, 50 ml of acetone, 0.17 g of triethylamine, and 0.35 g of p-toluenesulfonyl chloride were added thereto, and the mixture was stirred for reaction for 4.5 h. After the reaction, the mixture was concentrated under reduced pressure, washed with ethanol, and dried to obtain p-toluenesulfonate polyvinyl alcohol;
[0037] (2) dissolving 5 g of p-toluenesulfonate polyvinyl alcohol and 0.75 g of potassium phthalimide in N,N-dimethylformamide, heating at 100° C. under N2 protection for 3 h, concentrating under reduced pressure after the reaction, adding the product to ethanol, adding hydrazine hydrate, heating to 80° C. and reflux for 3 h, removing the solvent by rotary evaporation, washing with ethanol and drying to obtain amino polyvinyl alcohol;
[0038] (3) adding 1 g of carboxylated carbon nanotubes into a flask filled with toluene solvent, stirring evenly, then adding 2 g of amino polyvinyl alcohol, 4 g of N,N'-dicyclohexylcarbodiimide and 0.8 g of 4-dimethylaminopyridine, and heating to 120°C for reaction for 5 h, filtering after the reaction, washing with ethanol and drying to obtain carbon nanotube-grafted polyvinyl alcohol;
[0039] (4) dispersing the carbon nanotube grafted polyvinyl alcohol in a dimethyl sulfoxide solvent, spinning in a wet spinning machine, squeezing the solution into a spinning hole at a spinning temperature of 70°C and a nitrogen pressure of 0.1 MPa, and entering a coagulation bath of -10°C methanol. After the nascent fiber is coagulated in the coagulation bath, it is wound and rolled up, and coagulated after being soaked in methanol for 14 hours, and then naturally dried for 18 hours. The dried fiber is gradually heat-treated and stretched at a heat treatment temperature of 200°C and a stretching multiple of 12 times to obtain a high-performance carbon nanotube grafted polyvinyl alcohol composite fiber;
[0040] (5) First, 50 kg of silicate cement, 50 kg of fly ash powder, 15 kg of silica fume, and 75 kg of quartz sand were put into a mixer and stirred for 10 minutes to mix the dry materials evenly. Then, 35 kg of water and 0.4 kg of polycarboxylic acid water reducer were slowly added and stirred continuously to obtain a uniformly flowing cement slurry. The mixer was controlled to operate at a low speed. Then, 1.5% of the volume of the cement slurry was added with carbon nanotube grafted polyvinyl alcohol composite fibers, 0.4% of the volume of the cement slurry was added with steel fibers, and 1.5% of the volume of the cement slurry was added with ultra-high molecular weight polyethylene fibers. The materials were fully stirred and dispersed evenly. The materials were layered and cast into test specimens. After curing at room temperature for 24 hours, the mold was removed. Then, the test specimens were moved to a standard curing room for curing for 28 days to obtain a composite fiber reinforced cement-based material based on the hybrid effect.
[0041] Example 4
[0042] (1) At room temperature, 2 g of polyvinyl alcohol was placed in a flask, 50 ml of acetone, 0.24 g of triethylamine, and 0.5 g of p-toluenesulfonyl chloride were added thereto, and the mixture was stirred for 6 h. After the reaction, the mixture was concentrated under reduced pressure, washed with ethanol, and dried to obtain p-toluenesulfonate polyvinyl alcohol;
[0043] (2) dissolving 5 g of p-toluenesulfonate polyvinyl alcohol and 1.1 g of potassium phthalimide in N,N-dimethylformamide, heating at 120° C. under N2 protection for 4 h, concentrating under reduced pressure after the reaction, adding the product to ethanol, adding hydrazine hydrate, heating to 80° C. and reflux for 3 h, removing the solvent by rotary evaporation, washing with ethanol and drying to obtain amino polyvinyl alcohol;
[0044] (3) adding 1 g of carboxylated carbon nanotubes into a flask filled with toluene solvent, stirring evenly, then adding 3.5 g of amino polyvinyl alcohol, 2.7 g of N,N'-dicyclohexylcarbodiimide and 1.6 g of 4-dimethylaminopyridine, and heating to 105 ° C. for 6.5 h. After the reaction, filtering, washing with ethanol and drying to obtain carbon nanotube-grafted polyvinyl alcohol;
[0045] (4) dispersing the carbon nanotube grafted polyvinyl alcohol in a dimethyl sulfoxide solvent, spinning in a wet spinning machine, squeezing the solution into a spinning hole at a spinning temperature of 70°C and a nitrogen pressure of 0.1 MPa, and entering a coagulation bath of -20°C methanol. After the nascent fibers are coagulated in the coagulation bath, they are wound and rolled up, and coagulated after being immersed in methanol for 12 hours, and then naturally dried for 21 hours. The dried fibers are gradually heat-treated and stretched at a heat treatment temperature of 200°C and a stretching multiple of 12 times to obtain high-performance carbon nanotube grafted polyvinyl alcohol composite fibers;
[0046] (5) First, 50 kg of silicate cement, 40 kg of fly ash powder, 15 kg of silica ash, and 50 kg of quartz sand were put into a mixer and stirred for 2 minutes to mix the dry materials evenly. Then, 25 kg of water and 0.4 kg of polycarboxylic acid water reducer were slowly added and stirred continuously to obtain a uniformly flowing cement slurry. The mixer was controlled to operate at a low speed. Then, 0.6% of the volume of the cement slurry was added with carbon nanotube grafted polyvinyl alcohol composite fiber, 0.4% of the volume of the cement slurry was added with steel fiber, and 2% of the volume of the cement slurry was added with ultra-high molecular weight polyethylene fiber. The mixture was stirred and dispersed evenly. The materials were layered and cast into test specimens. After curing at room temperature for 24 hours, the mold was removed. Then, the test specimens were moved to a standard curing room for curing for 7 days to obtain a composite fiber reinforced cement-based material based on the hybrid effect.
[0047] Example 5
[0048] (1) At room temperature, 2 g of polyvinyl alcohol is placed in a flask, 50 ml of acetone, 0.1 g of triethylamine, and 0.5 g of p-toluenesulfonyl chloride are added thereto, and the mixture is stirred for reaction for 3 h. After the reaction, the mixture is concentrated under reduced pressure, washed with ethanol, and dried to obtain p-toluenesulfonate polyvinyl alcohol;
[0049] (2) dissolving 5 g of p-toluenesulfonate polyvinyl alcohol and 1.5 g of potassium phthalimide in N,N-dimethylformamide, heating at 140° C. under N2 protection for 5 h, concentrating under reduced pressure after the reaction, adding the product to ethanol, adding hydrazine hydrate, heating to 80° C. and reflux for 6 h, removing the solvent by rotary evaporation, washing with ethanol and drying to obtain amino polyvinyl alcohol;
[0050] (3) adding 1 g of carboxylated carbon nanotubes into a flask containing toluene solvent, stirring evenly, then adding 5 g of amino polyvinyl alcohol, 4 g of N,N'-dicyclohexylcarbodiimide and 2.5 g of 4-dimethylaminopyridine, and heating to 120°C for reaction for 8 h, filtering after the reaction, washing with ethanol and drying to obtain carbon nanotube-grafted polyvinyl alcohol;
[0051] (4) dispersing the carbon nanotube grafted polyvinyl alcohol in a dimethyl sulfoxide solvent, spinning in a wet spinning machine, squeezing the solution into a spinning hole at a spinning temperature of 60°C and a nitrogen pressure of 0.1 MPa, and entering a coagulation bath of -20°C methanol. After the nascent fiber is coagulated in the coagulation bath, it is wound and rolled up, and coagulated after being soaked in methanol for 10 hours, and then naturally dried for 18 hours. The dried fiber is gradually heat-treated and stretched at a heat treatment temperature of 180°C and a stretching multiple of 10 times to obtain a high-performance carbon nanotube grafted polyvinyl alcohol composite fiber;
[0052] (5) First, 50 kg of silicate cement, 30 kg of fly ash powder, 5 kg of silica fume, and 50 kg of quartz sand were put into a mixer and stirred for 2 minutes to mix the dry materials evenly. Then, 15 kg of water and 0.15 kg of polycarboxylic acid water reducer were slowly added and stirred continuously to obtain a uniformly flowing cement slurry. The mixer was controlled to operate at a low speed. Then, 1.5% of the volume of the cement slurry was added with carbon nanotube grafted polyvinyl alcohol composite fibers, 0.3% of the volume of the cement slurry was added with steel fibers, and 1% of the volume of the cement slurry was added with ultra-high molecular weight polyethylene fibers. The mixture was stirred and dispersed evenly. The materials were layered and cast into test specimens. After curing at room temperature for 18 hours, the mold was removed. Then, the test specimens were moved to a standard curing room for curing for 7 days to obtain a composite fiber reinforced cement-based material based on the hybrid effect.
[0053] Comparative Example 1
[0054] (1) First, 50 kg of silicate cement, 30 kg of fly ash powder, 15 kg of silica fume, and 75 kg of quartz sand were put into a mixer and stirred for 10 minutes to mix the dry materials evenly. Then, 25 kg of water and 0.4 kg of polycarboxylate water reducer were slowly added and stirred continuously to obtain a uniformly flowing cement slurry. The mixer was controlled to operate at a low speed, and then 0.4% of steel fiber and 1.5% of ultra-high molecular weight polyethylene fiber were added to the cement slurry by volume. The mixture was stirred and dispersed evenly. The materials were layered and cast into test specimens. After curing at room temperature for 24 hours, the mold was removed. Then, the test specimens were moved to a standard curing room for curing for 28 days to obtain cement-based materials.
[0055] Referring to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", GB / T5486-2008 "Test Methods for Inorganic Rigid Insulation Products" and GB / T10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulation Materials - Guarded Hot Plate Method", the flexural strength, compressive strength, density, flexural strength, flexural softening coefficient and thermal conductivity of cement-based materials are tested.
[0056] The bending properties of composite fiber reinforced cement-based materials were tested using thin plate specimens and beam specimens. The tests were carried out on a closed-loop hydraulic servo material testing machine with a loading rate of 0.5 mm / min and a closed-loop hydraulic servo material testing machine with a loading rate of 0.1 mm / min, respectively. The loading method was three-point loading.
[0057] Load sensors and LVDT are used to measure the bending load, and the IMC fully automatic data acquisition and processing system is used to collect and process the load and deformation data. Prismatic specimens and cubic specimens are used in the test to determine the compressive properties of composite fiber reinforced cement-based materials.
[0058]
[0059] The composite fiber reinforced cement-based material synthesized in Example 3 has the largest anti-softening coefficient, reaching 0.56. The composite fiber reinforced cement-based material synthesized in Example 5 has the largest thermal conductivity, reaching 0.063 W (mK) -1 . The composite fiber reinforced cement-based material synthesized in Example 2 has the largest flexural strength, reaching 14.10 MPa. The composite fiber reinforced cement-based material synthesized in Example 4 has the largest compressive strength, reaching 6.37 MPa. The composite fiber reinforced cement-based material synthesized in Example 5 has the largest elastic modulus, reaching 21.1 GPa. The cement-based material of Comparative Example 1 does not have high-performance carbon nanotube grafted polyvinyl alcohol composite fibers added, and its mechanical properties are not good.
Claims
1. A method for synthesizing a composite fiber reinforced cement-based material based on hybrid effect, characterized in that: The synthesis method is: (1) placing polyvinyl alcohol in a flask, adding acetone, triethylamine and p-toluenesulfonyl chloride thereto and stirring for reaction, concentrating under reduced pressure after the reaction, washing with ethanol and drying to obtain p-toluenesulfonate polyvinyl alcohol; (2) dissolving p-toluenesulfonate polyvinyl alcohol and potassium phthalimide in a mass ratio of 1:0.15-0.3 in N,N-dimethylformamide, heating and reacting for 3-5 hours at a temperature of 100-140° C. under N2 protection, concentrating under reduced pressure after the reaction, adding the product to ethanol, and adding hydrazine hydrate, reflux reaction for 3-6 hours, rotary evaporation to remove the solvent, washing with ethanol and drying to obtain amino polyvinyl alcohol; (3) adding the carboxylated carbon nanotubes into a flask containing toluene solvent, stirring evenly, then adding amino polyvinyl alcohol, N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and heating to react, filtering after the reaction, washing with ethanol and drying to obtain carbon nanotube-grafted polyvinyl alcohol; (4) dispersing the carbon nanotube grafted polyvinyl alcohol in a dimethyl sulfoxide solvent, spinning in a wet spinning machine, squeezing the solution into a spinning hole at a spinning temperature of 60-80°C and a nitrogen pressure of 0.1-0.2 MPa, and entering a coagulation bath of methanol at -20°C to -10°C. After the nascent fiber is coagulated in the coagulation bath, it is wound and rolled up, and coagulated after being soaked in methanol for 10-14 hours, and then naturally dried for 18-24 hours. The dried fiber is gradually heat-treated and stretched at a heat treatment temperature of 180-240°C and a stretching multiple of 10-14 times to obtain a high-performance carbon nanotube grafted polyvinyl alcohol composite fiber; (5) First, silicate cement, fly ash powder, silica fume, and quartz sand are put into a mixer and stirred for 2-10 minutes to mix the dry materials evenly. Then, water and polycarboxylic acid water reducer are slowly added and stirred continuously to obtain a uniformly flowing cement slurry. The mixer is controlled to operate at a low speed. Then, carbon nanotube-grafted polyvinyl alcohol composite fibers, steel fibers, and ultra-high molecular weight polyethylene fibers are added thereto. The materials are fully stirred and dispersed evenly. The materials are layered and cast into test specimens. After curing at room temperature for 18-24 hours, the mold is removed. Then, the test specimens are moved to a standard curing room for curing for 7-28 days to obtain a composite fiber-reinforced cement-based material based on a hybrid effect.
2. The method for synthesizing a composite fiber reinforced cement-based material based on hybrid effect according to claim 1, characterized in that: The mass ratio of polyvinyl alcohol, p-toluenesulfonyl chloride and triethylamine in (1) is 1:0.1-0.25:0.05-0.
12.
3. The method for synthesizing a composite fiber reinforced cement-based material based on hybrid effect according to claim 1, characterized in that: The reaction in (1) is carried out at room temperature for 3-6 hours.
4. The method for synthesizing a composite fiber reinforced cement-based material based on hybrid effect according to claim 1, characterized in that: In the above (3), the mass ratio of carboxylated carbon nanotubes, amino polyvinyl alcohol, N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 1:2-5:1.5-4:0.8-2.
5.
5. The method for synthesizing a composite fiber reinforced cement-based material based on hybrid effect according to claim 1, characterized in that: The heating reaction temperature in (3) is 90-120° C., and the reaction time is 5-8 h.
6. The method for synthesizing a composite fiber reinforced cement-based material based on hybrid effect according to claim 1, characterized in that: The mass ratio of silicate cement, fly ash powder, silica fume, quartz sand, water and polycarboxylate water reducer in (5) is 1:0.6-1:0.1-0.3:1-1.5:0.3-0.7:0.003-0.
008.
7. The method for synthesizing a composite fiber reinforced cement-based material based on hybrid effect according to claim 1, characterized in that: In the above (5), the volume addition amounts of carbon nanotube grafted polyvinyl alcohol composite fiber, steel fiber and ultra-high molecular weight polyethylene fiber are 0.6-1.5%, 0.3-0.6% and 1-2% of the cement paste respectively.
Citation Information
Patent Citations
Double-stage coal burner with internal flame stabilizer
CN101737772A
AUPQ544900A0